Tgf-β stimulated glycosaminoglycan (GAG) biosynthetic gene expression in vascular smooth muscle cells - Rostam, Muhamad Ashraf; Piva, Terence J.; Osman, Narin; Little, Peter J. (2013)
The pre-inflammatory stage of atherosclerosis is associated with proteoglycan glycosaminoglycan (GAG) chain hyperelongation that results in increased proteoglycan binding to low density lipoprotein (LDL). Transforming Growth Factor-β (TGF-β) is closely associated with atherosclerosis and mediates GAG chain hyperelongation.TGF-β signals through phosphorylation of Smad 2/3 at its C-terminus and it can also activate other kinases to phosphorylate Smad in the linker region. In vascular smooth muscle cells (VSMC) GAG chain hyperelongation is dependent upon transcription and translation but the targets of TGF-β signalling, most likely genes for GAG enzymes, remain unknown. A recent study by Anggraeni et al showed that GAG enzymes C4ST-1 and ChGn-2 involved in chondroitin sulphate (CS) GAG elongation have higher levels of expression in a mouse model of atherosclerosis.